TASYJI’UL LUGHOH AS A MICRO-IMMERSION MODEL: STRENGTHENING ARABIC PROFICIENCY THROUGH WEEKLY LANGUAGE INTERVENTION IN MODERN ISLAMIC BOARDING SCHOOL CONTEXT - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Siti Nikmatul Rochma; Nuraeni Rahmawati (Jurnal Manajemen Pendidikan, 2026)
This study examines Tasyji'ul Lughoh as a micro-immersion model to strengthen Arabic proficiency in a modern Islamic boarding school. Unlike full immersion that requires continuous exposure, this model offers structured weekly interventions. Using a qualitative case study design, data were collected through participant observation, semi-structured interviews, and document analysis involving teachers, student coordinators, and santriwati. The findings reveal four key mechanisms: (1) structured weekly exposure sustaining linguistic input, (2) collective error correction (islah lughah) enhancing grammatical awareness, (3) socially reinforced interaction fostering language habit formation, and (4) affective engagement increasing learners’ confidence and willingness to communicate. These interconnected elements form a holistic language learning ecosystem integrating cognitive, social, and emotional dimensions. This study introduces micro-immersion as a flexible and scalable alternative to full immersion, particularly in contexts with limited language exposure. The findings have significant implications for language pedagogy and institutional policy, emphasizing the importance of structured, socially embedded, and sustainable language interventions to achieve communicative competence.